Antifungal activity, mycotoxin inhibitory efficacy, and mode of action of hop essential oil nanoemulsion against Fusarium graminearum. (30th January 2023) - Jiang, Haiyang; Zhong, Shaobin; Schwarz, Paul; Chen, Bingcan; Rao, Jiajia
Graphical abstract: Highlights: The top chemical constituents of hop essential oil (HEO) were β-Myrcene and humulene. HEO nanoemulsion could inhibit the mycelial growth and spore germination. The production of deoxynivalenol (DON) could be suppressed by HEO nanoemulsion. HEO nanoemulsion altered the contents of total lipid and chitin in outer cell membrane. The permeability of cytoplasmic membrane was also increased. Abstract: This work aims to investigate antifungal, mycotoxin inhibitory efficacy of the hop essential oil (HEO) nanoemulsion and their mode of action (MOA) against Fusarium graminearum isolate, a fungal pathogen causing Fusarium Head Blight (FHB) in cereal crops. The HEO, primarily consisting of terpenes and terpenoids, was encapsulated in nanoemulsion droplets. Physically stable HEO-in-water nanoemulsion was fabricated using 0.5 wt% of tween 80 and 5 wt% oil phase comprising 30 % of Ostwald ripening inhibitor and 70 % of HEO. In terms of antifungal effect, HEO nanoemulsion could not only effectively inhibit mycelial growth and spore germination of F. graminearum isolates, but also remarkably suppress the production of deoxynivalenol (DON) and its derivatives in rice culture by applying 750 μg of HEO/g rice. Our studies on the MOA showed that HEO nanoemulsion could alter the contents of total lipid and chitin in outer cell membrane as well as damaging cytoplasmic membrane.